Performance analysis of a thermal energy storage system connected to a cooling tower for chilled water production of radiant ceiling - Farzaneh Rabbani; Mehdi Nasrabadi; Alireza Zolfaghari (مجله مدل سازی در مهندسی, 2000)
Thermal energy storage systems can reduce the need for energy during peak demand times. In this system, energy is stored during non-peak times and is used during peak demand times. In this research, the performance of the energy storage system in connection with the cooling tower as a sole cooling source of radiant ceiling system has been assessed. Since the performance of the cooling tower depends on the environmental conditions, the performance of the cited cooling system has been investigated in different climate zones. The performance of this system has been evaluated in four cities of Tehran, Shiraz, Tabriz and Bandar Abbas, which are representative of temperate and humid, hot and dry, cold and hot and humid climates respectively. The results presented that by storing the chilled water which is produced by the cooling tower in non-peak hours and using this water in peak hours, the maximum COP of the cooling system could increase to 8.5, 14, 12 and 10 in cities of Tehran, Shiraz, Tabriz and Bandar Abbas, respectively. Furthermore, it can be seen that after implementation of the mentioned cooling system, the chilled water temperature of radiant ceiling system is at least 2 to 3°C lower than the temperature of the water which is provided by the tower in majority of occupant attendance hours, especially during peak demand times. The results indicated that the proposed cooling system in Tehran with a temperate climate is able to provide thermal comfort conditions in 90% of attendance times.